Effects of lead mineralogy on soil washing enhanced by ferric salts as extracting and oxidizing agents. (October 2017) - Yoo, Jong-Chan; Park, Sang-Min; Yoon, Geun-Seok; Tsang, Daniel C.W.; Baek, Kitae
Abstract: In this study, we evaluated the feasibility of using ferric salts including FeCl3 and Fe(NO3 )3 as extracting and oxidizing agents for a soil washing process to remediate Pb-contaminated soils. We treated various Pb minerals including PbO, PbCO3, Pb3 (CO3 )2 (OH)2, PbSO4, PbS, and Pb5 (PO4 )3 (OH) using ferric salts, and compared our results with those obtained using common washing agents of HCl, HNO3, disodium-ethylenediaminetetra-acetic acid (Na2 -EDTA), and citric acid. The use of 50 mM Fe(NO3 )3 extracted significantly more Pb (above 96% extraction) from Pb minerals except PbSO4 (below 55% extraction) compared to the other washing agents. In contrast, washing processes using FeCl3 and HCl were not effective for extraction from Pb minerals because of PbCl2 precipitation. Yet, the newly formed PbCl2 could be dissolved by subsequent wash with distilled water under acidic conditions. When applying our washing method to remediate field-contaminated soil from a shooting range that had high concentrations of Pb3 (CO3 )2 (OH)2 and PbCO3, we extracted more Pb (approximately 99% extraction) from the soil using 100 mM Fe(NO3 )3 than other washing agents at the same process conditions. Our results show that ferric salts can be alternative washing agents for Pb-contaminated soils in view of their extracting and oxidizing abilities. Graphical abstract: Highlights: Ferric iron has the ability to extract and oxidize Pb minerals. Ferric iron oxidized PbS with reduction of ferric and oxidation of sulfide. PbSO4 was not dissolved by protons due to an insoluble mineral in acidic condition. Extractants including chloride ions formed PbCl2 precipitation. Ferric iron can be used as an alternative to remediating metal-contaminated soil.